The landscape of genetic variations in non-syndromic primary ovarian insufficiency in the MENA region: a systematic review - Allouch, Asma; Al-Barazenji, Tara; Al-Shafai, Mashael; Abdallah, Atiyeh M. (Frontiers in Endocrinology, 2024)
This systematic review speaks directly to the aims of your Research Topic, namely describing and understanding the genetic basis of female reproductive failure, especially in light of molecular genetics testing. Premature ovarian insufficiency (POI) is a primary cause of infertility with variable clinical manifestations. POI is a multifactorial disease with both environmental and known genetic etiologies, but data on the genetic variations associated with POI in the Middle East and North Africa (MENA) region are scarce. Knowledge about the genetic basis of POI in the Middle East paves the way for implementation of precision medicine in specific populations and informs the entire global community about the spectrum of causative mutations.We therefore searched the PubMed, Science Direct, ProQuest, and Embase databases for all reports of genetic variants associated with POI in the MENA region. Clinical and genetic data were collected from eligible articles, and variants were verified in ClinVar and PubMed NCBI (dbSNP). In performing our review, which is presented according to PRISMA guidelines, we establish that:  Of 1,803 studies, 25 met the inclusion criteria. Fifteen studies were case-control studies and 10 were case reports representing 1,080 POI patients. Seventy-nine variants in 25 genes associated with POI were reported in ten MENA countries. Of the 79 variants, 46 were rare and 33 were common variants. Of the 46 rare variants, 19 were pathogenic or likely pathogenic according to ACMG/AMP guidelines and ClinVar. No clear phenotype-genotype association was observed. Male family members carrying pathogenic variants also had infertility problems.This study therefore highlights how technological advances have facilitated the discovery of several new genes that may cause POI, partially explaining its heterogeneity. The analysis allows us to discuss the potential mechanistic basis of these potentially causative genes, but it also highlights the need for functional studies to definitively assess the underlying molecular mechanisms and the pathways responsible for POI. Nevertheless, this knowledge of the genetic basis of POI in the MENA region paves the way for implementation of precision medicine in specific patient populations.